2006
DOI: 10.1152/ajplung.00507.2005
|View full text |Cite
|
Sign up to set email alerts
|

SERPINB1 upregulation is associated with in vivo complex formation with neutrophil elastase and cathepsin G in a baboon model of bronchopulmonary dysplasia

Abstract: Bronchopulmonary dysplasia (BPD) continues to be a major cause of morbidity in premature infants. An imbalance between neutrophil elastase and its inhibitors has been implicated in BPD. Serine protease inhibitor (SERPIN)B1 is an inhibitor of neutrophil proteases, including neutrophil elastase (NE) and cathepsin G (cat G). Recent studies suggest that SERPINB1 could provide protection in the airways by regulating excess protease activity associated with inflammatory lung disorders. In this study, we determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 55 publications
1
46
0
Order By: Relevance
“…NE is a potent serine proteinase, responsible for tissue destruction in adult lung with emphysema (36). In the preterm newborn lung, increased NE activity affects lung remodeling and increases alveolar epithelial apoptosis and the development of BPD (15,16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NE is a potent serine proteinase, responsible for tissue destruction in adult lung with emphysema (36). In the preterm newborn lung, increased NE activity affects lung remodeling and increases alveolar epithelial apoptosis and the development of BPD (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Total inflammatory cell numbers as well as neutrophils were significantly decreased by rhSP-D ( Figure 4A). Increased NE activity has been associated with development of BPD (15,16). The addition of rhSP-D to Survanta decreased NE activity in the lung ( Figure 4B).…”
Section: Rhsp-d Treatment Decreased Pulmonary Inflammationmentioning
confidence: 93%
See 1 more Smart Citation
“…89 Yasumatsu et al probed SERPINB1 function in the established baboon BPD model. 90,91 As in humans, SERPINB1 was localized to bronchial and glandular epithelial cells, as well as mast cells, neutrophils and macrophages in the baboon lung.…”
Section: -22mentioning
confidence: 86%
“…90 These results suggested that SERPINB1 function in the newborn lung is critical as an antipeptidase shield against elastases associated with inflammation and responsible for lung injury.…”
mentioning
confidence: 92%